IMPLEMENTASI MODEL DEEP LEARNING (6CS) UNTUK MENINGKATKAN KREATIVITAS MUSIK DIGITAL SISWA SMP - Erinawaty Situmorang; Jaeni; Yahfenel Evi Fussalam (CV. ADIBA AISHA AMIRA, 2025)
This academic article seeks to address the relevance crisis in education, which is reflected in the declining engagement of lower secondary students, by integrating the Deep Learning (DL) framework and the six Global Competencies (6Cs). DL provides a systemic response to developing the potential of all learners, particularly those at the junior secondary level who are prone to disengagement. The learning models employed is Project-Based Learning (PBL), framed within the Collaborative Inquiry cycle, and supported by a cloud-based collaborative Digital Audio Workstation (DAW) application, such as Soundtrap. This approach aligns with the DL principle of Leveraging Digital, ensuring technology serves as an inclusive learning accelerator, supporting the equity hypothesis by being accessible across various devices. Impact measurement focuses on enhancing Creativity and Collaboration. Creativity is assessed based on the originality of composition and sound design, while Collaboration is evaluated by the quality of constructive peer-review interactions and active multi-track contributions within the DAW. Academic rigor is ensured through the use of New Measures (Learning Progressions rubrics) validated via the Collaborative Moderation process. These exploratory findings indicate that digital music PBL is highly effective in transforming student roles into co-designers and activators, yielding measurable gains in both key competencies. This conclusion affirms the role of collaborative technology as a DL catalyst, providing practical implications for the implementation of the Merdeka Curriculum in achieving measurable 21st-century skill goals